2021
DOI: 10.15252/embr.202051882
|View full text |Cite
|
Sign up to set email alerts
|

Npas4 regulates medium spiny neuron physiology and gates cocaine‐induced hyperlocomotion

Abstract: We show here that the transcription factor Npas4 is an important regulator of medium spiny neuron spine density and electrophysiological parameters and that it determines the magnitude of cocaine‐induced hyperlocomotion in mice. Npas4 is induced by synaptic stimuli that cause calcium influx, but not dopaminergic or PKA‐stimulating input, in mouse medium spiny neurons and human iPSC‐derived forebrain organoids. This induction is independent of ubiquitous kinase pathways such as PKA and MAPK cascades, and instea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…In pyramidal neurons, it is reported to enhance inhibitory synaptic transmission, while in somatostatin-positive interneurons, it augments excitatory synaptic transmission 33,[35][36][37][39][40][41][42] ; however, the role of NPAS4 in regulating striatal circuits and SUD-related plasticity and behavior is poorly understood. NPAS4 is induced rapidly and transiently in a small subset of NAc neurons during cocaine conditioning, and its NAc expression is required for cocaine CPP 43 and cocaine locomotor sensitization 44 , but also see data herein and 43 . Therefore, investigating the role of NAc NPAS4 in promoting drug-seeking behaviors and maintaining the D1/D2 activity balance addresses a significant knowledge gap.…”
Section: Introductionmentioning
confidence: 69%
“…In pyramidal neurons, it is reported to enhance inhibitory synaptic transmission, while in somatostatin-positive interneurons, it augments excitatory synaptic transmission 33,[35][36][37][39][40][41][42] ; however, the role of NPAS4 in regulating striatal circuits and SUD-related plasticity and behavior is poorly understood. NPAS4 is induced rapidly and transiently in a small subset of NAc neurons during cocaine conditioning, and its NAc expression is required for cocaine CPP 43 and cocaine locomotor sensitization 44 , but also see data herein and 43 . Therefore, investigating the role of NAc NPAS4 in promoting drug-seeking behaviors and maintaining the D1/D2 activity balance addresses a significant knowledge gap.…”
Section: Introductionmentioning
confidence: 69%
“…It should be highlighted that the larger change observed in DLPFC can also be attributed to its larger sample size. It has been previously demonstrated that NPAS4 plays a role in memory (Sun & Lin, 2016), modulating inhibitory-excitatory balance (Lin et al, 2008; Opsomer et al, 2020; Spiegel et al, 2014), epileptogenesis in mice, cocaine-induced hyperlocomotion (Lissek et al, 2021), cognitive well-being and many other diseases (Coutellier et al, 2012; Fu et al, 2020; Funahashi et al, 2019; Maya-Vetencourt, 2013). While the association between NPAS4 and MDD has been shown in mice previously (Jaehne et al, 2015), we validated the same relationship for humans and multiple brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…DeltaFosb, an alternative splice variant of Fosb, regulates cocaine-induced locomotor behavior [129] and reward [123]. Npas4 controls several parameters of medium spiny neuron physiology and cocaine-induced locomotor responses [130], as well as conditioned place preference [131].…”
Section: Addictionmentioning
confidence: 99%
“…They also oftentimes allow the conceptual bridging of organizational levels in that molecular alterations have defined effects on tissue organization which in turn leads to differences in organism function and behavior. An example is Npas4's dependency on cellular input [130,230], subsequent cell-type specific remodeling [35,130] and then specific influence on behavior [34,130].…”
Section: The Universality Of Adaptive Transcriptionmentioning
confidence: 99%